Examining the Impact of Gender on Young People's Views of Forced Marriage in Britain. (January 2017) - Gill, Aisha K.; Harvey, Heather
This article examines survey and interview responses from British Asian youths, primarily Muslims, to consider (a) this group's perceptions of forced marriage (FM), along with their preconceptions around it, and (b) the ways in which they exercise their right not to marry. The findings suggest that learned discriminatory values and norms regarding gender roles remain integral to how marriage is perceived and how FM is perpetrated and experienced. Whereas women tend to be more compliant regarding their parents' and family's wishes, men are often motivated by a sense of pride and masculinity. Initiatives intended to understand FM, support the recovery of victims, and prevent the practice would benefit from incorporating a consciously gendered understanding, to actively challenge the socially constructed gender roles of affected communities.